Extraction Quality of Porang Flour Due to Chip Flour Treatment and Ethanol Concentration - Herawati Heny; Anggraeni Dian; Kurniasari Indah; Kusnandar Feri; Suparlan; Agustinisari Iceu; Sunarmani; Bachtiar Muchamad; Zubaidi Thohir; Misgiyarta; Bin Arif Abdullah; Hernani; et al. (E3S Web of Conferences, 2023)
Porang tuber has a high potential for glucomannan levels. Improving the quality of porang tubers can be done by extracting dry chips from porang tubers. One alternative is to combine the process of using ethanol as a reagent to produce good quality porang flour. The purpose of the research activity is to modify dried chip porang flour using several ethanol concentrations for extraction and to characterize its products. The research methodology was carried out using two types of porang flour (brown and yellow) and ethanol concentrations (50, 70, and 90%). The data analyzed with SPSS 24 software. The research resulted the different treatments resulted in significantly different yield quality, moisture content, and ash content between treatments. The highest glucomannan content 66.94% and the highest whiteness index 82.08 was found in the extraction process using dried yellow chip with 90% ethanol concentration process technology. For further research, it is necessary to conduct a stepwise extraction to study the influence of varying ethanol concentrations in order to increase the glucomannan content.